Nonlinear Frequency Offset Optimization Strategy for Solving Secondary Range Ambiguity in Planar FDA-STAP Radar - Sun, Yan; Shao, Shuai; Wang, Wen-Qin; Greco, Maria Sabrina; Gini, Fulvio; Zhang, Shunsheng (IEEE transactions on aerospace and electronic systems, 2025)
Frequency diverse array (FDA) radar enjoys a remarkable benefit in range ambiguous clutter suppression thanks to its range dependency of transmitting beam pattern. However, a linear frequency offset can cause secondary range ambiguity problems that deteriorate the clutter suppression performance. To address this problem, we propose here a nonlinear frequency offset optimization strategy for planar FDA-space time adaptive processing radar. In this article, our study first formulates a space-time-range signal model of a planar FDA radar. Based on the analysis of the secondary range ambiguity, we address the nonlinear frequency offset optimization problem and propose an improved search algorithm with fast convergence to solve it. Numerical analysis is carried out to verify the validity of the proposed nonlinear strategy to remove the secondary range ambiguity problem and maintain a high range-dimensional beam resolution.